Evaluasi Diagnostik pada Mata Kuliah Praktikum Pengukuran Listrik Teknik Elektro Universitas Negeri Padang - Sri Wahyuni; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to review, explain, express problems, and find out the process of implementing the practicum, the difficulties in the practicum, and the factors causing the difficulties in the practicum in the Electrical Measurement Practicum Course using the illuminative evaluation model. The informants in this study were 24 students of the UNP Electrical Engineering Education study program. The research method used is a qualitative method with descriptive evaluative data. Data collection techniques in this method using interviews and documentation. Data analysis techniques using data analysis according to Miles Huberman are data collection, data reduction, data display, and drawing conclusions. The results of the study concluded that the process of carrying out the electrical measurement practicum had gone well and smoothly in accordance with the standard operating procedure of the practicum, there were several difficulties in the practicum experienced by students including: difficulty reading and understanding circuit drawings, difficulty in assembling tools and materials in the circuit, difficulty using and read the results on several measuring instruments. The cause of the difficulty is due to the lack of understanding of students in understanding the electrical measurement material and the worksheets that have been given as well as the learning environment. Recommendations given to overcome difficulties in electrical measurement practicum should be carried out as much as possible so that other difficulties do not occur again.